2018
DOI: 10.3233/jad-171031
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Driving Study Investigating Self-Regulation Behavior in Early Alzheimer’s Disease: A Pilot Study

Abstract: This pilot study used a naturalistic approach to accurately show that AD drivers have poorer tactical self-regulation behavior than healthy older drivers. Future deployment of assistance systems in vehicles should specifically target tactical self-regulation components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 51 publications
(87 reference statements)
1
16
0
8
Order By: Relevance
“…Awareness can be assessed at the level of performance (online) monitoring, and research has demonstrated the contribution of this aspect of awareness to overall functioning, using error detection methods, for example. 72 - 74 Although these metamemory studies, as well as some naturalistic studies 64 , 69 , 75 investigate error responses and/or evaluation of performance after a test, only a few validated measures of awareness incorporate this approach, such as MARS, MAFS, and CMT. Online monitoring of performance is an ability that could be targeted in goal-orientated cognitive rehabilitation programs, 76 and testing awareness at this level would be a useful component of a clinical tool to direct interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness can be assessed at the level of performance (online) monitoring, and research has demonstrated the contribution of this aspect of awareness to overall functioning, using error detection methods, for example. 72 - 74 Although these metamemory studies, as well as some naturalistic studies 64 , 69 , 75 investigate error responses and/or evaluation of performance after a test, only a few validated measures of awareness incorporate this approach, such as MARS, MAFS, and CMT. Online monitoring of performance is an ability that could be targeted in goal-orientated cognitive rehabilitation programs, 76 and testing awareness at this level would be a useful component of a clinical tool to direct interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining naturalistic driving behavior among persons with normal cognition and those with cognitive impairment have typically used in-car cameras [1618, 38, 39], although use of OBD II-connected data loggers, as in this study, is increasing [19, 20]. The differences found in this study are consistent with previous studies comparing persons with symptomatic AD and controls [16], but provide further insight demonstrating that differences in naturalistic driving behavior are evident even during the long preclinical stage of AD.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior work showing that AD drivers whose naturalistic driving was video recorded showed poorer tactical self-regulation behavior and made twice as many critical events as healthy older drivers. They were also three times more likely to be unaware of these events (Paire-Ficout et al, 2018). Unfortunately, the early AD group may need to continue to use compensatory strategies (i.e., cautious driving) to prevent more egregious safety errors and accidents.…”
Section: Discussionmentioning
confidence: 99%